The Red Sea.. Features of Conflict Cooperation Opportunities (Global Journal of Human-Social Science, 2022)
Abstract not found
Keywords: conflict – cooperation – security – red sea – horn of africa – suez canal –bab al-mandab – piracy – gulf security